PENGARUH EFIKASI DIRI TERHADAP NIAT BERWIRAUSAHA PADA SISWA SMK ISLAM TERPADU SMART INFORMATIKA SURAKARTA - M.Ali Mursidi; Mursid Dwi Hastomo; Sri Partini; Tri Wuryanto (JURNAL ILMIAH EDUNOMIKA, 2026)
The increasing unemployment rate and limited job opportunities in Indonesia necessitate the development of entrepreneurial intentions, particularly among the younger generation. This study aims to determine the influence of self-efficacy on entrepreneurial intention among students at SMK Islam Terpadu Smart Informatika Surakarta. A quantitative approach was employed, with the research population consisting of 12th-grade students. A sample of 121 students was selected using total sampling. Data were collected through questionnaires and analyzed using linear regression. The results indicate that self-efficacy has a positive and significant effect on entrepreneurial intention, meaning that higher student self-efficacy is associated with a stronger intention to start a business. In conclusion, fostering self-efficacy is crucial for promoting entrepreneurship among vocational students. It is recommended that schools enhance their curricula by incorporating practical business experiences, such as school bazaars, to provide students with real-world exposure and strengthen their entrepreneurial intentions. Keywords: self-efficacy, entrepreneurial intention, vocational high school students